Acute toxicity and antimicrobial activity of the Plume Poppy extract (Macleaya microcarpa (Maxim.) Fedde.) - Voloshchuk, Natalia; Harnyk, Myroslava; Nazarchuk, Oleksandr; Ocheretniuk, Anna; Bilyk, Oksana (ScienceRise: Biological Science, 2025)
Modern medicine is facing a global problem of increasing antibiotic resistance, which significantly limits the effectiveness of traditional antibacterial drugs. This necessitates the search for new sources of antimicrobial agents, among which plant extracts containing biologically active substances with antibacterial and antifungal properties are of particular interest. The aim was a study of the acute toxicity and antimicrobial activity of Plume Poppy herb dry extract. Material and Methods. The study objects were: Plume Poppy herb, which was harvested in the Vinnytsia region during the flowering period in the summer of 2023; the dry extract of Plume Poppy herb, obtained by extraction and evaporation. The study of the acute toxicity of the Plume Poppy herb dry extract by intragastric administration to mice was carried out using the express method of T.V. Pastushenko. The study of the antimicrobial activity of the Plume Poppy herb dry extract was carried out using the disk-diffusion method and the method of two-fold serial dilutions on the basis of the Microbiology Department laboratory of National Pirogov Memorial Medical University, Vinnytsia. Results. According to the classification of K.K. Sidorov, the dry extract of Plume Poppy herb is classified as class III - moderately toxic substances. LD₅₀ was 149 mg/kg for males and 174 mg/kg for females. A pronounced direct antimicrobial activity of the Plume Poppy herb dry extract has been established. The specified extract exhibits moderate antistaphylococcal activity, acts on vegetative forms of bacilli, inhibits the growth of yeast-like fungi of the genus Candida and at the same time is less effective against gram-negative bacteria. Conclusions. The Plume Poppy herb is a source of biologically active compounds and represents a promising raw material for the development of new herbal medicinal products for external use, particularly dry extracts and their solutions with pronounced antimicrobial activity